Practical Guide to Equine Colic. - Southwood, Louise (Wiley, 2012)
Practical Guide to Equine Colic takes a step-by-step clinical approach to the medical management of this common condition. Covering colic management and treatment from the veterinarian's first involvement through referral, surgical intervention, and long-term recovery, the book offers practical advice on managing a colic case. Designed for easy navigation, chapters are brief and fully cross-referenced, allowing the reader to quickly find and apply information in the practice setting. The book incorporates key points, checklists, clinical tips, step-by-step illustrations, and case examples, e.